Prinsip dan Landasan Hukum Ekonomi Islam - Nuruddin Armanto (Fakultas Ekonomi dan Bisnis Islam, 2020)
Economics has a certain character that is distinguished by other understandings. An understanding, including economics, is built by a purpose, principles, values, and paradigms. For example, the understanding of liberalism was built on the goal of the realization of the freedom of each individual to develop himself. This freedom will be realized if every individual has the same opportunity to develop. Therefore, equal opportunity is a principle that will be held which will eventually give birth to a paradigm of free competition. Islamic economics is built for holy purposes guided by the teachings of Islam and achieved in a way that is also guided by the teachings of Islam. Therefore, all of these are interrelated and structured hierarchically, in the sense that the Islamic economic spirit is reflected in its objectives, and supported by pillars, the goal to achieve falah can only be (Islamic values), and operational pillars, which are reflected in economic principles (Islamic principles). From this will appear an Islamic economic building in a paradigm, both paradigms in thinking and behave as well as the shape of the economy. The pillar of Islamic economics is moral. It is only with the morality of Islam that the building of Islamic economics can be erected and only with Islamic economics can falh be achieved. Islamic morality stands on a postulate of faith and a postulate of worship. The essence and moral of Islam is monotheism. The implication of monotheism, that Islamic economics has a transcendental nature (not secular), where the role of God in all aspects of the economy becomes absolute.